Role of artificial intelligence in banking and finance - Rita Jain (Journal of Management and Science, 2023)
The integration of artificial intelligence (AI) in banking and finance has revolutionized the industry by enhancing efficiency, accuracy, and customer experience. This research paper provides an in-depth analysis of the use of AI in banking and finance, examining its various applications such as fraud detection, credit scoring, customer service, and investment management. By reviewing the existing literature, this paper aims to explore the benefits and challenges associated with AI implementation in the financial sector. The findings reveal that AI technologies have significantly improved decision-making processes, reduced operational costs, and increased overall profitability. However, concerns related to data privacy, bias, and ethical implications must be carefully addressed to ensure the responsible and sustainable use of AI in the future.